A Porphyrin-DNA Chiroptical Molecular Ruler With Base Pair Resolution - Burns, Jonathan R.; Wood, James W.; Stulz, Eugen (Frontiers in Chemistry, 2020)
DNA-based molecular rulers enable scientists to determine important parameters across biology, from the measurement of protein binding interactions, to the study of membrane dynamics in cells. However existing rulers can suffer from poor nanometre resolution due to the flexible nature of linkers used to tether to the DNA framework. We aimed to overcome this problem using zinc and free-base porphyrin chromophores attached via short and rigid acetylene linkers. This connectivity enables the distance and angle between the porphyrins to be fine-tuned along the DNA scaffold. The porphyrins undergo favourable energy transfer and chiral exciton coupling interactions to act as highly sensitive molecular ruler probes. To validate the system, we monitored the detection of small changes in DNA structure upon intercalation of ethidium bromide. CD spectroscopy showed the porphyrins undergo highly sensitive changes in excitation coupling to facilitate base pair resolution of the novel system.